Termination of Bleeding by a Specific, Anti-catalytic Antibody to Plasmin - Zhao, Tieqiang (J Thromb Haemost, 2019)
BACKGROUND: Excessive, plasmin-mediated fibrinolysis augments bleeding and contributes to death in some patients. Current therapies for fibrinolytic bleeding are limited by modest efficacy, low potency and off-target effects. OBJECTIVES: To determine whether an antibody directed against unique loop structures of the plasmin protease domain may have enhanced specificity and potency for blocking plasmin activity, fibrinolysis and experimental hemorrhage. METHODS: The binding specificity, affinity, protease cross-reactivity, and antifibrinolytic properties of a monoclonal plasmin inhibitor antibody (Pi) were examined and compared to epsilon aminocaproic acid (EACA), a clinically used fibrinolysis inhibitor. RESULTS: The Pi specifically recognized loop 5 of the protease domain and did not bind to other serine proteases or nine other non-primate plasminogens. By comparison to EACA, the Pi was ~7 logs more potent for neutralizing plasmin cleavage of small molecular substrates and >3 logs more potent for quenching fibrinolysis. When compared to α2-antiplasmin, the most potent covalent inhibitor of plasmin, the Pi was similarly effective for blocking catalysis of a small molecular substrate and was a more potent fibrinolysis inhibitor. Fab or chimerized Fab fragments of the Pi were equivalently effective. In vivo, in a humanized model of fibrinolytic surgical bleeding, the Pi significantly reduced bleeding more than a clinical dose of EACA. CONCLUSIONS: A monoclonal antibody directed to unique loop sequences in the protease domain, is a highly specific, potent, competitive plasmin inhibitor that significantly reduces experimental surgical bleeding in vivo.